INFLUENCE OF ASCORBIC ACID ON EGG QUALITY - SOUZA,Pedro Alves de (2001)
The egg quality may be influenced by some nutrients added to laying hens diets and among these nutrients, the ascorbic acid is included. According to some researches, this acid, besides of improving the quality, it can increase the egg production and weight. In addition, it reduces the quantity of cracked eggs and food intake. In order to contribute with more information, this experiment was developed. Concentrations of 100; 150 and 200mg/kg of ascorbic acid were added to rations of laying hens during 60 days, with the objective of determining the influence of ascorbic acid on the quality of eggs kept under room temperature conditions (26.7 ± 2.2°C and 60 ± 5% moisture) for a period of 28 days. A total of 1440 eggs were used, being 720 of white shell and 720 of brown shell. Egg quality was determined by Haugh unit and yolk index, every 7 days. The obtained results allowed to conclude that ascorbic acid, independent on the level of supplementation, was not enough to decrease.